Social and cultural factors leading to the marriage of minors (Journal of the College of Education for Women, 2019)
This paper deals with the most important factors leading to child marriage and the importance of the study shed light on the factors leading to the marriage of minors than to underage marriage of repercussions on society and on the individual and household level, and thus its effects on the development of Almrah Battabarha half of society Vsba minors hinders progress Almrah and deprive of her childhood and deprive them of education leading to the spread of illiteracy , in addition to the marriage of minors having psychological risks, health and social girl and the family together.The objectives of the study focused on identifying the socio and cultural factors leading to the marriage of minors, and highlights the marriage Alqaasrataly the girl effect.